Morphology and Piezoelectric Properties of Diphenylalanine Microcrystals Grown from Methanol-Water Solution - Zelenovskiy, P. S.
Morphology and piezoelectric properties of diphenylalanine microcrystals grown by drying the droplet of methanol and water mixture in various proportions have been studied. We have found that the increase of water concentration leads to the significant change of the microcrystal morphology from flat dendrite structures to elongated microcrystals: microtubes and microrods. The effect was attributed to increasing of the drying time. The morphology of the dendrite structures was revealed and empirical dependence of the dendrite thickness on diameter was found. Finally, the piezoelectric activity of the microtubes was demonstrated using the piezoresponse force microscopy.